Mediporus, a new genus of the leafhopper subfamily Evacanthinae (Hemiptera: Cicadellidae), with a key to genera of the Evacanthini - Wang, Yang; Viraktamath, Chandra A.; Zhang, Yalin (Zootaxa, 2015)
Mediporus splendens gen. n. and sp. n. is described and illustrated based on specimens from Thailand. In addition, a key to genera of the Evacanthini is provided.